Supply and demand of ecosystem service provision in relation to dynamics land-cover changes: a remote sensing and geospatial analysis in Sukabumi Regency - Fitriani, Ananda; Dimyati, Muhammad; Zulkarnain, Faris (International Journal of Electrical and Computer Engineering (IJECE), 2024)
The rate of population growth in Sukabumi Regency continues to grow, along with the increasing need for food. This population growth, combined with the constant changes in land cover can reduce the productivity of environment in providing natural capital for food availability. Therefore, this study aimed to examine the condition of ecosystem service provision for a decade in Sukabumi Regency due to changes in land cover. In general, the efficient use of remote sensing method and geographic information systems to monitor ecosystem services had received widespread recognition. Following this scenario, the current study used geospatial analysis with dasymetric method which was integrated with supply and demand formulas for ecosystem services provision, food availability, and remote sensing. Geographic information system was also used for land cover interpretation data. The results showed that three districts in Sukabumi Regency, namely Cicurug, Cibadak, and Cicantayan, had “exceeded” condition when the environmental condition already passed the threshold or were unable to support population's needs. Meanwhile, the other districts have “not exceeded” condition, when the environmental conditions were still able to fulfill the needs of population. Finally, the changes in agricultural land cover had a significant influence on the condition of ecosystem services.